Fine root Production in Evergreen Broadleaved Forest, Northeast Vietnam - Tran Van Do; Osamu Kozan; Le Xuan Truong; Nguyen Toan Thang; Dang Van Thuyet; Phung Dinh Trung; Nguyen Thi Thu Phuong (Open Journal of Plant Science - Peertechz Publications, 2016)
Estimating production of fi ne roots (diameter ≤ 2 mm) is signifi cant important to understand carbon cycle of forest ecosystem as it may contributes up to 70% of total net primary production. The estimation of fine root production is left behind in many parts, especially in developing countries including Vietnam. In this study, fi ne root production was estimated for tropical evergreen broadleaved forest in northeast of Vietnam using soil core sampling and litter bags by applying continuous infl ow method. Masses of live fine roots and of dead fi ne roots were collected in May and December 2014, and April 2015. ecomposition ratios of dead fi ne roots were estimated for May-December 2014 (summer/ growing season), and December 2014-May 2015 (winter). Results indicated that decomposition ratios were signifi cant different between summer (0.0022 day-1) and winter (0.0018 day-1). The difference of decomposition ratios resulted in difference of the fi ne root production (0.75 g m-2 d-1 in summer vs 0.35 g m-2 d-1 in winter). Throughout the year, fi ne root production in tropical evergreen broadleaved forest, northeast of Vietnam was 0.55 g m-2 d-1.